Empowering the Community or Corporate Image Building?: Analysis of Rengganis Agro Tourism (WAR) in Gunung Gambir Area by PT. Perkebunan Nusantara (PTPN) XII - Febriyanti, Maya Putri; Hendrijanto, Kris; Poerwanti, Sari Dewi (WELFARE : Jurnal Ilmu Kesejahteraan Sosial, 2023)
PT. Perkebunan Nusantara (PTPN) XII, as part of its corporate social responsibility, aims to enhance economic activity in the Mount Gambir area through Agro Rengganis Tourism (WAR), with the primary goal of fostering image development through empowerment. This qualitative study seeks to identify the various motives underlying empowerment initiatives in the Mount Gambir region, employing the theory of legitimacy as its perspective. The research reveals that PTPN XII employs an independence model in its empowerment process, focusing on improving community welfare via Rengganis Agro Tourism. This model involves providing the community with the autonomy to identify and harness the potential of their natural surroundings. PTPN serves as a facilitator, offering necessary developmental support such as training and education. This approach proves effective in elevating the standard of living for the local population. However, the study highlights a notable gap in the sustainability aspect of the empowerment process. The current program tends to prioritize image-building and maintaining positive relations between PTPN XII and the community, potentially overlooking long-term sustainability efforts. Keywords: Community empowerment, agrotourism, social welfare   Peningkatan aktivitas perekonomian di kawasan Gunung Gambir melalui Wisata Agro Rengganis (WAR) yang difasilitasi PT. Perkebunan Nusantara (PTPN) XII sebagai bagian dari tanggung jawab sosial perusahaan mengindikasikan motif pembangunan citra dalam bentuk pemberdayaan. Penelitian ini bertujuan untuk mengidentifikasi beragam motif yang muncul dari kegiatan pemberdayaan di kawasan Gunung Gambir dengan menggunakan metode kualitatif. Perspektif yang digunakan dalam penelitian ini menggunakan teori legitimasi. Penelitian ini menemukan bahwa proses pemberdayaan yang dilakukan PTPN XII untuk meningkatkan kesejahteraan masyarakat melalui Wisata Agro Rengganis ditempuh dengan model kemandirian. Masyarakat diberikan ruang terbuka untuk menentukan dan mengembangkan potensi alam. PTPN berperan sebagai fasilitator yang menyediakan kebutuhan pengembangan, seperti pelatihan dan pendidikan. Mekanisme ini merupakan langkah efektif yang dapat meningkatkan taraf hidup masyarakat sekitar. Meskipun demikian, upaya keberlanjutan tidak menjadi bagian dari proses pemberdayaan, sehingga program yang dijalankan bertendensi pada pembangunan citra yang tujuannya hanya untuk menjaga hubungan baik antara PTPN XII dengan masyarakat demi keberlanjutan perusahaan. Kata Kunci: Community empowerment, agrotourism, social welfare